Linguistic resources and strategies used in multilingual communication in HIV/AIDS care centres in Lesotho - Sobane, Konosoang; Anthonissen, Christine (Stellenbosch Papers in Linguistics Plus, 2014)
This paper gives a description of multilingual practices in two HIV-care centres in Lesotho on the basis of interviews with both healthcare providers and some patients who make use of the services of these centres. It considers the importance of effective linguistic communication in HIV-care and the hazards posed to such communication when physicians do not share the first language of the patients and of others working in these healthcare facilities. It gives the insights gained in a recent study on the kinds of interventions developed to facilitate communication in such multilingual institutional settings. In one of the centres informal interpreters are appointed to assist in transfer of information during consultations; in the second centre interpreting is only casually available from bilingual staff members. Besides interpreting, participants reported engaging in a number of other mediating practices. Evidence gained from informal interpreting studies elsewhere suggests that more than literal translation is required to achieve the kind of communicative success that will ensure quality in the healthcare provided to a vulnerable community. This study agrees with such findings and has generated a number of suggestions for improving the management of the linguistic diversity in communication within such clinics. The paper focuses on the specific resources provided in the healthcare centres and on the strategies participants use to enhance medical communication.